2007
DOI: 10.1345/aph.1h550
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statin Therapy in Sepsis

Abstract: There is an association between statin use and a lower incidence of sepsis and sepsis-related mortality. However, a causal relationship between statin use and reduced sepsis-related mortality has not yet been established. Currently, statins cannot be recommended for sepsis prevention or treatment until controlled trials are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…In vitro studies have suggested that statins have beneficial immunomodulatory effects, which extend from their anti-oxidative and antiinflammatory properties, including the suppression of G protein-mediated inflammation (which may also impede bacterial replication), the reduction of cytokine expression and acute phase reactants after coronary artery bypass, improvements in endothelial function and thrombomodulation, and reduction in the expression of the matrix metalloproteinases that impair host inflammatory response [2,3]. However, other studies [4,5] have raised questions about whether this apparent benefit against infection is real or merely associated with unmeasured confounders, and a recent systematic review [6] found that, although 6 of the 7 observational studies to have examined this topic reported that statin use reduced the risk of sepsis, these studies had a number of methodologic limitations that prevented definitive conclusions.…”
mentioning
confidence: 99%
“…In vitro studies have suggested that statins have beneficial immunomodulatory effects, which extend from their anti-oxidative and antiinflammatory properties, including the suppression of G protein-mediated inflammation (which may also impede bacterial replication), the reduction of cytokine expression and acute phase reactants after coronary artery bypass, improvements in endothelial function and thrombomodulation, and reduction in the expression of the matrix metalloproteinases that impair host inflammatory response [2,3]. However, other studies [4,5] have raised questions about whether this apparent benefit against infection is real or merely associated with unmeasured confounders, and a recent systematic review [6] found that, although 6 of the 7 observational studies to have examined this topic reported that statin use reduced the risk of sepsis, these studies had a number of methodologic limitations that prevented definitive conclusions.…”
mentioning
confidence: 99%
“…These mechanisms appear to be active in the physiologic response to shock caused by sepsis [10,11]. In animal models, the mechanism appears to be the reduction of inflammatory mediators and final common pathway products, such as heat shock proteins, tumor necrosis factor-a, multiple interleukins, nuclear factor jB, nitric oxide synthetase (and, therefore, nitric oxide), and oxidized low-density lipoproteins [1][2][3][4][5][6][7][8][9]. These biologic end products indicted as causative in the physiologic derangements of septic shock are also associated with hemorrhagic shock as a putative final common pathway to organ dysfunction and death.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amounts of research suggest that this class of drugs may have many other potential physiological effects besides the blockade of HMG Co-A reductase. Animal studies show that statins have potent anti-inflammatory effects [1][2][3] by reducing a vast number of inflammatory mediators, including heat shock proteins [4], tumor necrosis factor-a, various interleukins, nitric oxide synthetase, oxidized low-density lipoproteins, and oxygen free radicals [5][6][7][8][9]. The effects on humans have been studied retrospectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bei -leider -noch fehlenden prospektiven Studien müssen allerdings auch die "Skeptiker" gehört werden ({Zitat 20 in [12]}, [7,12] …”
Section: Sepsis Und Modsunclassified